Growth, nutrition and efficiency in the transport, uptake and use of nutrients in african mahogany - Souza, Aline; Smiderle, Oscar; Chagas, Edvan; Alves, Márcia; Fagundes, Paulo Roberto (Revista Ciência Agronômica, 2020)
African mahogany is a species preferred by many entrepreneurs as an investment in the forestry sector. However, there are few studies or research on the species, especially in Brazil. The aim of this work was to study the efficiency of nutrient uptake, accumulation, distribution and use in Khaya ivorensis and Khaya senegalensis, in addition to aspects of growth variables and of dry matter partitioning as a function of mineral fertilisation. Morphological, physiological and nutritional parameters were determined in the African mahogany plants 140 days after transplanting (DAT). The greatest zinc (Zn) content was detected in the shoots of both the Khaya ivorensis and Khaya senegalensis plants, accounting for more than 50% of the accumulated total of the plants with added nutrient solution. Maintaining the plants of Khaya senegalensis and Khaya ivorensis with the use of nutrient solution provides the best conditions for nutrient use, and allows plants with excellent morphological and nutritional characteristics to be ready for the field within five months after transplanting in a shaded nursery. The most efficient uptake, transport and use of macro- and micronutrients is found in the species Khaya senegalensis with the addition of nutrient solution.